Activation of mTOR: a culprit of Alzheimer’s disease? - Cai Z (Dove Medical Press, 2015)
Zhiyou Cai,1 Guanghui Chen,1 Wenbo He,1 Ming Xiao,2 Liang-Jun Yan31Department of Neurology, Renmin Hospital, Hubei University of Medicine, Shiyan Renmin Hospital, Shiyan, Hubei Province, People’s Republic of China; 2Department of Anatomy, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 3Department of Pharmacology and Neuroscience, University of North Texas Health Science Center, Fort Worth, TX, USA Abstract: Alzheimer’s disease (AD) is characterized by cognitive impairment in clinical presentation, and by β-amyloid (Aβ) production and the hyper-phosphorylation of tau in basic research. More highlights demonstrate that the activation of the mammalian target of rapamycin (mTOR) enhances Aβ generation and deposition by modulating amyloid precursor protein (APP) metabolism and upregulating β- and γ-secretases. mTOR, an inhibitor of autophagy, decreases Aβ clearance by scissoring autophagy function. mTOR regulates Aβ generation or Aβ clearance by regulating several key signaling pathways, including phosphoinositide 3-kinase (PI3-K)/protein kinase B (Akt), glycogen synthase kinase 3 [GSK-3], AMP-activated protein kinase (AMPK), and insulin/insulin-like growth factor 1 (IGF-1). The activation of mTOR is also a contributor to aberrant hyperphosphorylated tau. Rapamycin, the inhibitor of mTOR, may mitigate cognitive impairment and inhibit the pathologies associated with amyloid plaques and neurofibrillary tangles by promoting autophagy. Furthermore, the upstream and downstream components of mTOR signaling are involved in the pathogenesis and progression of AD. Hence, inhibiting the activation of mTOR may be an important therapeutic target for AD. Keywords: Alzheimer’s disease, mammalian target of rapamycin, rapamycin, β-amyloid, neurofibrillary tangles, signaling